Reliabilitas dan Validitas The Light-Moran Positive Empathy Scale-15 pada Mahasiswa Indonesia - Veronica; Hanifah (Jurnal Ilmu Perilaku, 2025)
Empathy is a change in emotional state that results from reflecting on the emotional state of others and experiencing an emotional quality similar to the emotions experienced by other people. The Light-Moran Positive Empathy Scale (PES-15) was developed to measure positive emotional responses to others’ emotional expressions. This study aims to adapt Light-Moran PES-15 and test the validity and reliability of the Indonesian version of Light-Moran PES-15. A total of 101 Indonesian students participated by completing the Indonesian version of Light-Moran PES-15. Data were analyzed using descriptive statistics, Cronbach’s alpha, corrected item-total correlation, and CFA. The Cronbach's alpha result = 0.89 with each dimension being 0.79 and 0.83. Item-total correlation = 0.39 – 0.72. CFI = 1.00, TLI = 1.00, NFI = 0.981 RMSEA = 0.00. This shows that this measuring instrument can be trusted and is able to measure the level of positive empathy with the Indonesian student population. This study provides an important contribution to the development of empathy measurement tool in Indonesia.